Cicer turcicum: A New Cicer Species and Its Potential to Improve Chickpea - Toker, Cengiz; Berger, Jens; Eker, Tuba; Sari, Duygu; Sari, Hatice; Gokturk, Ramazan Suleyman; Kahraman, Abdullah; Aydin, Bilal; von Wettberg, Eric J. (Frontiers in Plant Science, 2021)
Genetic resources of the genus Cicer L. are not only limited when compared to other important food legumes and major cereal crops but also, they include several endemic species with endangered status based on the criteria of the International Union for Conservation of Nature. The chief threats to endemic and endangered Cicer species are over-grazing and habitat change in their natural environments driven by climate changes. During a collection mission in east and south-east Anatolia (Turkey), a new Cicer species was discovered, proposed here as C. turcicum Toker, Berger & Gokturk. Here we describe the morphological characteristics, images, and ecology of the species, and present preliminary evidence of its potential utility for chickpea improvement. C. turcicum is an annual species, endemic to southeast Anatolia and to date has only been located in a single population distant from any other known annual Cicer species. It belongs to section Cicer M. Pop. of the subgenus Pseudononis M. Pop. of the genus Cicer L. (Fabaceae) and on the basis of internal transcribed spacer (ITS) sequence similarity appears to be a sister species of C. reticulatum Ladiz. and C. echinospermum P.H. Davis, both of which are inter-fertile with domestic chickpea (C. arietinum L.). With the addition of C. turcicum, the genus Cicer now comprises 10 annual and 36 perennial species. As a preliminary evaluation of its potential for chickpea improvement two accessions of C. turcicum were field screened for reproductive heat tolerance and seeds were tested for bruchid resistance alongside a representative group of wild and domestic annual Cicer species. C. turcicum expressed the highest heat tolerance and similar bruchid resistance as C. judaicum Boiss. and C. pinnatifidum Juab. & Sp., neither of which are in the primary genepool of domestic chickpea. Given that C. arietinum and C. reticulatum returned the lowest and the second lowest tolerance and resistance scores, C. turcicum may hold much potential for chickpea improvement if its close relatedness supports interspecific hybridization with the cultigen. Crossing experiments are currently underway to explore this question.